Perbandingan Penerapan Strategi Critical Incident dengan Strategi Mind Mapping dalam Pembelajaran Menulis Puisi Siswa Kelas VIII SMP Negeri L Sidoharjo - Noermanzah N.; M Nurdin Rais; Nur Nisai Muslihah (Jurnal Perspektif Pendidikan, 2013)
This thesis titled "Comparison The Application Of Strategy Critical Incident With Strategy Mind Mapping in Learning Writing Poetry Students' Classroom VIII SMP Negeri L. Sidoharjo” Research problem, "is there any significant difference between the application of strategies critical incident with the strategy mind mapping in learning to write poetry graders VIII SMP Negeri L. Sidoharjo? Destination the research, "for know the difference who significant between the application of strategy Critical Incident with strategy Mind Mapping in learning writing poetry students' classroom VIII SMP Negeri L. Sidoharjo Types of experiment research pure. Population the research entire students classroom VIII SMP Negeri L. Sidoharjo totaled 174 students. Two class as samples selected "were randomly flocking" namely, the class VIII.2 as experimental I class with implementing the strategy critical incident and class VIII.3 as experimental II class with applying strategy mind mapping. Number of each class of samples 34 students. Data collection techniques tests. The acquisition value of the average pretest experimental I class 66.7 and experimental II class 66.9, whereas postes experimental I class 80.2 and experimental II class is 78.4. Acquisition data is were analyzed with test-t at significant level 0,05 = 2,00. Based on the calculation known to t (1,21) < t (2,00) Ho is accepted, then the not the existence of differences who significant in learning writing poetry students' classroom. VIII SMP Negeri L. Sidoharjo. with applying strategy of Critical Incident and strategies Mind Mapping.